The Function of Prophetic Forthtelling in Roho Christianity - Bariu, Richard Mutura (European Scientific Journal, ESJ, 2017)
This paper examines the forms and function of prophecy in Roho (Spirit-led) Christianity in Africa. It seeks to situate this function within the rubric of biblical prophecy. It takes seriously their beliefs and theological reasoning that informs their practice. We look at forms of biblical prophecy that generally serve as their guiding principle, namely: foretelling and forthtelling. The literature available on Roho Christianity largely focuses on the historical, sociological, and anthropological aspects of this brand of Christianity. Majority of scholars have paid attention to their origins, rituals, and interaction with the larger society. While this is important, there is very little attention given to one of their principal characteristics–an active prophetic ministry. This paper seeks to satisfy the following seven objectives. Firstly, we look at the prophetic role of the church in African society. Secondly, we try to establish the nexus between prophecy and salvation in Roho Christianity. Thirdly, we look at the forthtelling character and function of Jewish prophecy. Fourthly, we look at prophecy as a community constitution in Roho churches. Fifthly, we assess how prophecy acts as group ritual for identity maintenance. Sixthly, we examine ways in which prophecy acts as symbolic Christian ethics. Finally, we explore how prophetic forthtelling enhances socioeconomic support among Roho churches. In order to achieve the foregoing, we look at concepts common to Roho Christianity in an attempt to draw conclusions about the concept and nature of prophecy in Roho churches and convictions connected with them.